Students’ Perceptions on Virtual Discussion of Learning English for Specific Purposes - Puspa Fortuna Zulfa (IJELR: International Journal of Education, Language, and Religion, 2023)
The learning process in this pandemic era triggers the enhancement of technology utilization. The virtual learning classroom is then used for compensating the absence of face to face learning process. It also happens in the learning process for English for specific purposes (ESP). This research is aimed at finding out and describing the students’ perceptions about virtual discussion conducted by the lecturer for some meetings according to the campus’ syllabus. The data is collected from questionnaire-interview (Questaview) containing some questions to enlist students’ views which are distributed to 3 classes, they are two Information System classes and an Accounting Information System class. The sample of this research is just 30% of the entire students which are 22 students. Then, for analyzing the data, the researcher describes the students’ opinion on virtual discussion of learning English for specific purposes and uses Likert scale. The result shows that virtual discussion has positive and negative effects to comprehend the material, less acceptance of English material, less practice, yet the flexibility of learning time and re-reading material can be approved by the students. At the last opinion, the students state their wishes in conducting double ways consecutively, both online and offline for obtaining the useful benefits from those two.